2014
DOI: 10.1123/smej.2011-0003
|View full text |Cite
|
Sign up to set email alerts
|

The Changing Climates of the Sport Management Academic Job Market and Doctoral Students’ Career Expectations

Abstract: Past research shows that the job market for sport management academic positions was strong, with more job openings than qualified professors to fill the positions. Due to changing global and higher education climates, however, it was necessary to conduct further research to examine how these shifts in the external environment have impacted the sport management job market. Therefore, this study employed a content analysis methodology to examine the faculty job openings in sport management from 2010 to 2011. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 5 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…This finding is consistent with the literature. In their study of sport management doctoral students' career expectations, Geurin- Eagleman and McNary (2014), found that less than a quarter of sport management doctoral students (24.7%) had taken a pedagogy course through their doctoral program, and only 18.5% had received guidance from their campus teaching and learning center. Not surprisingly, doctoral students within education programs are likely to be exposed to many more classes on pedagogy and/or curriculum development, and thus are more likely to have a better grasp on the linking of theory and practice across curriculum.…”
Section: Towards Experiential Learningmentioning
confidence: 99%
“…This finding is consistent with the literature. In their study of sport management doctoral students' career expectations, Geurin- Eagleman and McNary (2014), found that less than a quarter of sport management doctoral students (24.7%) had taken a pedagogy course through their doctoral program, and only 18.5% had received guidance from their campus teaching and learning center. Not surprisingly, doctoral students within education programs are likely to be exposed to many more classes on pedagogy and/or curriculum development, and thus are more likely to have a better grasp on the linking of theory and practice across curriculum.…”
Section: Towards Experiential Learningmentioning
confidence: 99%